Language teacher identity and language acquisition in a South Saami preschool : a narrative inquiry - Kroik, David (The Australian Journal of Indigenous Education, 2022)
This paper explores language teacher identity (LTI) among three preschool teachers. The focus lies on the preschool teachers’ identities as linguistic role models by means of analysing their own descriptions of language learning, that is, their personal experiences of and reflections on language acquisition. Three interviews were made with different in-service preschool teachers. The interviews were analysed by means of narrative inquiry and thematic analysis and guided by literature on LTI, as well as the researcher’s previous experience and knowledge of the current field. The findings illustrate how the teachers assumed a leading position in the South Saami language revitalisation project and cope with the responsibility tied to that position. The discussion of the narratives revolves around language teaching and learning made salient in the narrative process. The study provides a hopeful view of language revitalisation by showcasing that it is not only the expected first-language native speakers that are driving forces in the process of restoring a broken chain of intergenerational language transmission. It further illustrates a way for an Indigenous academic to investigate settings within their own community and collaborate with other stakeholders in a language revitalisation project to generate new insights on language revitalisation.